Technological and infrastructural issues of institutional repositories in university libraries in Nigeria: and the way forward (2019)
echnology and infrastructure are prerequisites in the development of any institutional repository (IR). These however constitute major issues contending with the sustenance of institutional repositories especially in the developing countries. Extant literature focused on the awareness, benefits and the various IR activities across the globe. This study investigated the technological and infrastructural challenges of institutional repositories in university libraries in Nigeria. The study adopted the descriptive survey research design. A multistage sampling procedure was employed to sample 844 lecturers of the universities in Nigeria and 8 heads of the digitization section of the libraries. Data generated were analyzed using descriptive statistics. The findings revealed that low bandwidth, inadequate and obsolete hardware and software components coupled with low server configuration, and erratic power supply, occasioned by poor funding are among the technological and infrastructural problems affecting institutional repositories in university libraries in Nigeria. The study advocated for the provision of more and sufficient bandwidth for the library system, good configuration of computer systems, the use of inverters and solar systems to ensure uninterrupted power supply and enhanced funding through special IR budgetary allocation by the universities’ management